Bridging Traditional and Digital Industrial Symbiosis: Comparative Insights From Croatia and Slovenia in the ESG and Digital Transformation Era - Unukić, Ivana (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
In the era of ESG and AI, industrial symbiosis (IS) represents a key strategy for achieving sustainable management. This paper presents a comparative analysis of two national approaches, Croatia’s traditional, material-based IS model and Slovenia’s digitally supported e-Simbioza platform, to explore how analogue and digital pathways can both contribute to ESG goals. Through qualitative analysis of secondary data and case studies, the research highlights how digitalization, including the use of ICT and potential applications of AI, can enhance symbiotic networks through improved coordination, transparency, and predictive analytics. While Croatia demonstrates strong industry-led practices, Slovenia’s approach emphasizes digital facilitation. The findings reveal a complementary relationship between traditional and digital models of IS, suggesting that AI and digital tools can gradually augment established IS practices. Despite regulatory and infrastructural barriers, this study offers insights for policymakers and businesses aiming to scale circular economy practices in the context of the green transition and digital transformation.